2011
DOI: 10.3189/172756411795931778
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of seasonal sea-ice thickness change in the Transpolar Drift observed by local ice mass-balance observations and floe-scale EM surveys

Abstract: International audienceNot Availabl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…the fact that the higher the frequency, the faster the wave propagation, and its dependence on the ice thickness, to invert the average thickness of Tara's floe. The results agreed well with electromagnetic measurements and drill hole profiles conducted on the same floe (Haas et al, 2011), thus validating the use of a classical concept (the dependence of wave propagation on ice thickness) to passively monitor sea ice thickness on a regular basis over horizontal scales from 10 0 to 10 2 km.…”
Section: Sea Ice Deformationsupporting
confidence: 75%
“…the fact that the higher the frequency, the faster the wave propagation, and its dependence on the ice thickness, to invert the average thickness of Tara's floe. The results agreed well with electromagnetic measurements and drill hole profiles conducted on the same floe (Haas et al, 2011), thus validating the use of a classical concept (the dependence of wave propagation on ice thickness) to passively monitor sea ice thickness on a regular basis over horizontal scales from 10 0 to 10 2 km.…”
Section: Sea Ice Deformationsupporting
confidence: 75%
“…They are however likely to be characteristic of the ice floe the three stations 1, 2, and 3 were placed on. Moreover, it should be noted that very little change in ice thickness was observed between May 8 and June 26, as shown by a repeat of the survey conducted along the same 2160 m-long line (Haas et al, 2011).…”
Section: Datamentioning
confidence: 94%
“…Haas et al (2011) have shown that the ice thickness shrinks by only a few cm over this time period. This change is less than the error of 0.2 m on our estimate, so that it is best to run the analysis on the whole 663 h to maximize the robustness of the estimation.…”
Section: A Ice Thicknessmentioning
confidence: 96%
See 2 more Smart Citations